Pengaruh Harga, Kuliatas Produk, dan Citra Merek Terhadap Keputusan Pembelian Produk Skintific - Andy Putri, Fransisca Wahyu Mei; Tresyanto, Citra Anggraini (Universitas Katolik Darma Cendika, 2025)
Changes in people's behavior can occur due to awareness of their daily needs. One of today's public awareness is the importance of maintaining healthy facial skin as a form of skin health investment. This condition creates a lifestyle of caring for facial skin with the help of various care products. Therefore, this phenomenon has given rise to a series of new brands of skincare products, one of which is the Skintific brand. The Skintific brand has a diverse target market, one of which is students. This study will discuss the Skintific brand with a focus on the dependent variable of purchasing decisions (Y) in students in East Surabaya. This study also aims to analyze and prove the influence of price (X1), product quality (X2), brand image (X3) on purchasing decisions. In processing the data, this study used a quantitative method with the SPSS 26 application. The sampling technique used was the probability sampling technique with a total of 100 East Surabaya students as respondents. The adjusted R square value was 53.3%, which means that the independent variable contributed moderately to the dependent variable. The t-test results showed that price (X1), product quality (X2), brand image (X3) had a positive and significant effect on purchasing decisions (Y).